2015
DOI: 10.1080/19349637.2015.985558
|View full text |Cite
|
Sign up to set email alerts
|

Purpose in Life and Well-Being: The Relationship Between Purpose in Life, Hope, Coping, and Inward Sensitivity Among First-Year University Students

Abstract: The present study investigated the relationship between purpose in life, hope, coping, and spiritual sensitivity among a sample of 166 first year psychology students. Family support and hopefulness predicted strong purpose in life. Inward sensitivity, together with agency thinking as part of hopefulness, notably increased the predictive variance of strong purpose in life. Positive correlations were also found between all variables, as well as low indications of suicidal ideation. These findings, particularly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
0
18
0
3
Order By: Relevance
“…One in five college students report having an active mental illness 1 and many young adults experience psychological distress during their first year of college. 2 This distress may negatively affect their academic performance, 1 mental well-being, [3][4][5][6] increase their health risk behaviors (substance use and sexual risk-taking [SRT]), 7-10 and increase their risk of suicide. 1 Suicide is the second leading cause of death in young adults 11 and 1.9% of college students report attempting suicide within the last year.…”
Section: Introductionmentioning
confidence: 99%
“…One in five college students report having an active mental illness 1 and many young adults experience psychological distress during their first year of college. 2 This distress may negatively affect their academic performance, 1 mental well-being, [3][4][5][6] increase their health risk behaviors (substance use and sexual risk-taking [SRT]), 7-10 and increase their risk of suicide. 1 Suicide is the second leading cause of death in young adults 11 and 1.9% of college students report attempting suicide within the last year.…”
Section: Introductionmentioning
confidence: 99%
“…From the above, we noted that hope is very important for all individuals who face stresses, such as patients to adapt with their disease. Several studies have found that hope has strong positive relations with a variety of psychological outcomes such as emotional adjustment and quality of life (Stoyles, Chadwick, & Caputi, 2015). In the same context, the results of the Foote etal (1990) study indicated a relationship between hope, social support and self-esteem in patients.…”
Section: Hope and Psychological Well-beingmentioning
confidence: 98%
“…From the above, we noted that hope is significant for all individuals who face stresses, such as patients, to adapt to their disease. Several studies have found that hope has strong positive relations with various psychological outcomes, such as emotional adjustment and quality of life [19]. Foote et al [20] indicated a relationship was found between hope, social support, and self-esteem in patients.…”
Section: Hope and Psychological Well-beingmentioning
confidence: 99%